PENGEMBANGAN MODUL FISIKA BERORIENTASI MODEL PEMBELAJARAN INQUIRY UNTUK PESERTA DIDIK - Vira Novia Riska; Rahmi Zulva; Silvi Trisna (Journal of Teaching and Learning Physics, 2021)
The purpose of this study was to create a physics module oriented to the inquiry learning model that is valid and practical due to the lack of attractive teaching materials. This research is a research and development using the inquiry model. The type of research used in this research is Research and Development (R&D). The subjects in this study were 28 educators and students. The research procedure used in this study is a 4-D model, namely define design, develop, and disseminate. The instruments used in this study were the product validation sheet and the product practicality sheet. Based on the validation results, it is found that the module has a very valid category with a percentage of 83.91% and a very practical category with a percentage of 92.65%. Modules can be used in the learning process in the classroom to help students understand.